Hypertension: What are Reasonable Goals for Therapy? - Vinall, Maria (MD Conference Express, 2011)
It is generally accepted that the risk of cardiac events increases as blood pressure increases and that even a small reduction in systolic blood pressure is associated with decreased risk. There is controversy, however, about how aggressively hypertension should be treated. This article reviews several important clinical trials on hypertension.